Efficacy and safety of dapagliflozin plus saxagliptin vs monotherapy as added to metformin in patients with type 2 diabetes: A meta-analysis. Issue 30 (24th July 2020) - Zhuang, Yan; Song, Jin; Ying, Miaofa; Li, Mingxing
Abstract: Background: This study aim at evaluating the efficacy and safety of dapagliflozin plus saxagliptin vs monotherapy as added to metformin in patients with type 2 diabetes mellitus (T2DM). Method: PubMed, Cochrane library, Embase, CNKI and Wanfang databases were searched up to 31 December 2019. Randomized controlled trials (RCTs) applicable in dapagliflozin plus saxagliptin vs monotherapy as added to metformin in the treatment of T2DM were included. The outcomes included changes in HbA1c, FPG, body weight, SBP, DBP and adverse reactions. Fixed or random effects model were used to assess these outcomes. Results: In this study, 8 RCTs involved 7346 patients were included. Compared with dapagliflozin plus metformin(DM) group, patients treated with dapagliflozin plus saxagliptin add on to metformin(DSM) could significantly increase the adjusted mean change levels of HbA1c, FPG, SBP and DBP( P  < .00001, SMD = −4.88, 95%CI = −6.93∼−2.83; P  < .00001, SMD = −6.50, 95%CI = −8.55∼−4.45; P  < .00001, SMD = −0.97, 95%CI = −1.15∼−0.78; P  < .00001, SMD = −2.00, 95%CI = −2.20∼−1.80), but no major difference in body weight loss showed( P  = .12, SMD = 0.92, 95%CI = −0.22∼2.06). Furthermore, DSM therapy displayed better effects than saxagliptin plus metformin(SM) in the adjusted mean change levels of HbA1c, FPG, body weight and SBP( P  < .00001, SMD = −7.75, 95%CI = −8.84∼−6.66; P  < .00001, SMD = −7.75, 95%CI = −8.84∼−6.66; P  = .04, SMD = −3.40, 95%CI = −6.64∼−0.17; P  = .04, SMD = −7.75, 95%CI = −8.84∼−6.66), whereas no obvious difference in lowering DBP( P  = .18, SMD = −16.35, 95%CI = −40.12∼7.41). Additionally, compared with DM and SM groups, there were no remarkable difference in the incidence of nausea, influenza, headache, diarrhea, urinary tract infection and renal failure for patients taking DSM, but the incidence of genital infection and hypoglycemia were higher in DSM group. Conclusions: Patients taking the DSM therapy had better effects in reducing the level of HbA1c, FPG, body weight, SBP and DBP than the DM and SM therapy. However, patients treated with DSM therapy are more likely to have hypoglycemia and genital infection. Dapagliflozin plus saxagliptin may be a suitable therapy strategy for patients with T2DM inadequately controlled with metformin, and this will provide a clinical reference for the treatment of T2DM. Abstract : Supplemental Digital Content is available in the text